ЗАГАЛЬНА ХАРАКТЕРИСТИКА ОБСТАВИНИ, ЩО ПОМ’ЯКШУЮТЬ АДМІНІСТРАТИВНУ ВІДПОВІДАЛЬНІСТЬ - Панасюк, Оксана Володимирівна (SUPREMANCE OF LAW, 2018)
The article is devoted to the scientific knowledge of domestic studies in the science of administrative and tort law in order to determine the nature of circumstances that mitigate administrative responsibility. The article addresses the problematic issues of applying each circumstance. The article substantiates the proposal to improve the content of the circumstance of “committing an offense to a pregnant woman or a woman who has a child under one year of age”. The author substantiates the importance of including an additional circumstance, which mitigates administrative liability in the list of Article 34 of the Code of Administrative Offenses.
Keywords: delinquent; circumstances mitigating administrative liability; offenses; general rules for imposing administrative penalties